ASESMEN MINAT DAN BAKAT: KUNCI PENGEMBANGAN KARIER YANG EFEKTIF DI SEKOLAH MENENGAH ATAS - Az-zahra, Caesaria; Salbiyah, Salbiyah; Adha, Hany Natari; Alrefi, Alrefi (Universitas Muria Kudus, 2025)
Assessment of interests and talents plays a crucial role in individual career planning, especially at the high school (SMA) level. This study aims to analyze the effectiveness of interest and talent assessments in enhancing students' self-understanding, facilitating appropriate career decision-making, and increasing learning motivation. The research method used is a systematic literature study by searching various scientific journal databases, such as Google Scholar, using keywords relevant to interest and talent assessment, career planning, and high school students. The selected articles were analyzed in-depth to identify the benefits of interest and talent assessment, effective implementation strategies, and potential challenges. The results of the research indicate that interest and talent assessments can increase learning motivation, involvement in extracurricular activities, and awareness of career opportunities. The application of this assessment also assists Guidance and Counseling (BK) teachers in providing more effective and targeted services. However, the implementation of this assessment also faces challenges such as limited resources, lack of student understanding regarding the benefits of assessment, as well as the validity and reliability of the assessment instruments used.